“I Like to Keep my Archaeology Dead”. Alienation and Othering of the Past as an Ethical Problem - Schreiber, Stefan; Neumann, Sabine; Egbers, Vera (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2019)
As archaeologists, we have to deal with the dead, and as David Clarke once said, we like to keep our archaeology dead. From an epistemological perspective, alienation from the dead seems almost inevitable; otherwise, we would only project today’s conditions onto the past. Therefore, the past must be, and must remain, a foreign country. These alienating processes have ethical implications, however, especially when it comes to the study of human remains. In this article, we analyze the structures within the scientific discipline of archaeology that normalize practices, such as the labeling of human bone material during excavations and the object-like display of skeletons in museums. We argue that archaeologists have an – often rejected – ethical responsibility towards subjects from the past. We, therefore, seek to open up a debate concerning alternative strategies for the treatment of the dead.